Clinical profile and outcome of rodenticide poisoning in patients admitted to a tertiary care teaching hospital in Mysore, Karnataka, India - Chikkaveeraiah, Shashidhara Kuppegala; Marijayanth, Manthappa; Reddy, Prabhath Kiran; Kaluvakuri, Sumanth (International Journal of Research in Medical Sciences, 2016)
Background: Rodenticide poisoning is of the major types of poisoning prevalent in India. However this broad category consists of different type of compounds with different mechanisms of toxicity and variable mortality rates. Methods: This study was performed on all cases of rodenticide poisonings admitted to a tertiary care hospital in Mysore between May 2014 and April 2015. Study consisted of 64 subjects. Results: 31 subjects had consumed aluminium phosphide, 18 had consumed Yellow Phosphorus and 12 had consumed Zinc Phosphide while 3 patients had consumed bromadiolone. There were 13 mortalities among the study group out of which 9 were in aluminium phosphide group while 4 were in the yellow phosphorus group. There were no mortalities in cases who had consumed zinc phosphide and bromodiolone. Conclusions: Aluminium phosphide was the most common compound rodenticide consumed and it was associated with increased mortality as compared to other Rodenticide poison.